2016
DOI: 10.1049/el.2015.3781
|View full text |Cite
|
Sign up to set email alerts
|

W‐band dual‐channel receiver with active power divider and temperature‐compensated circuit

Abstract: A W-band dual-channel receiver is presented for the frequency-modulated continuous wave radars. In order to improve the isolation between two RF channels, a compact active power divider is implemented by a dual-output local oscillator (LO) amplifier. The temperature-compensated circuit also mitigates the gain variation of the receiver according to the ambient temperature. The fabricated receiver integrated circuit shows a conversion gain of 16 dB, a noise figure of 6.4 dB, and an input 1 dB compression point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ma et al reported that by using an organic molecule (N-DMBI) for doping of ntype CP (FDBPPV), better carrier mobility was achieved by enhancing molecular packing. 215 Another example is PEDOT with preferential edge-on orientation when doped with PSS, Tos, or OTf, [216][217][218][219][220] while favoring face-on orientation when doped with smaller counter ions (like chloride Cl À ). 52,140 Although there is no limitation in exploiting different doping agents in the oCVD method, it generally was not a center of attention and only a fraction of the dopants are used for synthesis in practice.…”
Section: Doping (And Oxidants)mentioning
confidence: 99%
“…Ma et al reported that by using an organic molecule (N-DMBI) for doping of ntype CP (FDBPPV), better carrier mobility was achieved by enhancing molecular packing. 215 Another example is PEDOT with preferential edge-on orientation when doped with PSS, Tos, or OTf, [216][217][218][219][220] while favoring face-on orientation when doped with smaller counter ions (like chloride Cl À ). 52,140 Although there is no limitation in exploiting different doping agents in the oCVD method, it generally was not a center of attention and only a fraction of the dopants are used for synthesis in practice.…”
Section: Doping (And Oxidants)mentioning
confidence: 99%
“…Millimeter-wave frequencies including W-band (75-110 GHz) have short wavelengths and broad allocated bandwidth, which are beneficial for high resolution radars and high speed wireless communications [1][2][3][4][5]. In the millimeter-wave frequency range, a rectangular waveguide is generally adopted as a main transmission line instead of a coaxial cable due to the lower loss and easier manufacturability [6].…”
Section: Introductionmentioning
confidence: 99%
“…The reported power dividers [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] can be classified into active and passive types. Active power dividers usually use two common-drain FETs [ 13 ] or Darlington cell [ 14 ] topologies to achieve single-to-differential outputs by adopting advanced processes. Despite the advantage of compact size, active dividers are unsuitable for portable systems due to extra power dissipation.…”
Section: Introductionmentioning
confidence: 99%